2003
DOI: 10.1021/ac026216w
|View full text |Cite
|
Sign up to set email alerts
|

Polar Polymeric Stationary Phases for Normal-Phase HPLC Based on Monodisperse Macroporous Poly(2,3-dihydroxypropyl methacrylate-co-ethylene dimethacrylate) Beads

Abstract: The effect of variables such as shape template size, porogen composition and percentage, content of cross-linking monomer, and polymerization temperature on the properties of uniformly sized 3-microm porous poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads prepared by the staged templated suspension polymerization technique has been studied. The porous properties of the beads including surface morphology, pore size distribution, and specific surface area have been optimized to obtain highly efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Particles prepared for chromatography columns are packed into columns and back pressure is measured as an indication of mechanical strength for instance [300].…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Particles prepared for chromatography columns are packed into columns and back pressure is measured as an indication of mechanical strength for instance [300].…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…This is much lower than the reported method. 11 This result demonstrates that the beads possess high permeability.…”
mentioning
confidence: 78%
“…The testing of the organic polymer matrixes under normal-phase conditions is seldom reported. 8,9 Petro et al 10 and Xu et al 11 reported based on linear polystyrene beads (preparation by emulsification polymerization method) as seeds for preparation of macroporous poly(glycidymethacrylate-co-ethylenedimethacrylate) (P GMA/EDMA ) beads by using a two-step swelling and polymerization; then the hydrolysis of the beads were used as the NPLC stationary phase for the separation of a variety of polar compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we use mixtures of the two porogens to avoid formation of surface holes and simultaneously obtain beads with a smoother surface [20].…”
Section: Preparation Of Monodisperse Porous Beadsmentioning
confidence: 99%